Thermal stress, p53 structures and learning from elephants - Karakostis, Konstantinos; Padariya, Monikaben; Thermou, Aikaterini; Fåhraeus, Robin; Kalathiya, Umesh; Vollrath, Fritz (Cell death discovery, 2024)
As species adapt to climatic changes, temperature-dependent functions of p53 in development, metabolism and cancer will adapt as well. Structural analyses of p53 epitopes interacting in response to environmental stressors, such as heat, may uncover physiologically relevant functions of p53 in cell regulation and genomic adaptations. Here we explore the multiple p53 elephant paradigm with an experimentally validated in silico model showing that under heat stress some p53 copies escape negative regulation by the MDM2 E3 ubiquitin ligase. Multiple p53 isoforms have evolved naturally in the elephant thus presenting a unique experimental system to study the scope of p53 functions and the contribution of environmental stressors to DNA damage. We assert that fundamental insights derived from studies of a historically heat-challenged mammal will provide important insights directly relevant to human biology in the light of climate change when 'heat' may introduce novel challenges to our bodies and health.